Manufacturing systems and industry applications : selected, peer reviewed papers from the 2011 international conference on materials engineering for advanced technologies (ICMEAT 2011) May 5-6, 2011, Singapore, Singapore - Wu, Yanwen (Advanced materials research, 2011)
The 2011 International Conference on Materials Engineering for Advanced Technologies was held on May 5-6, 2011, in Singapore. The objective of the conference was to bring together researchers from academia and industry, as well as end-users, in order to share ideas, problems and solutions related to the multifaceted aspects of Materials Engineering for Advanced Technologies. The resultant timely overview will be appreciated by anyone involved in these fields. Review from Book News Inc.: Some 200 papers discuss such aspects as applying rough sets in customer classification, metaphor and interes.